Reemplazo de dinamita semexa 45% 7 7/8” por dinamita exsablock 45% 7 7/8 según condiciones geo mecánicas de la veta esperanza r.t. para tajos con cara libre concerniente a un tipo de roca mala, con el fin de reducir la sobre dilución del mineral en e.c.m comiluz sac, compañía minera marsa s. a. - Cruz Faustino, Evert Jesus (2018)
The present investigation intends to diminish the over dilution of the mineral with respect to the clearing in the blasting process which will lead to a better selectivity of the mineral since the granulometry of the blasting obtained tends to be adequate due to the fact that the fragmentation presents an average of 15 cms. . which allows us to choose the mineral dismantling to form our rumas, complying with the monthly program required and / or programmed, justifying the method of cutting and upward filling used for this vein due to the geo-mechanical conditions of the same, since it is presented in type of bad terrain, not only did the selectivity improve, but it also led to a reduction in costs in the sustaining process since there is less damage to the rock, with the lower power explosive having control over the height mining, having more time to do a better job favoring quality work without time pressures, reflected in a greater progress by meeting monthly requirements and / or established in the mining plan achieving an increase in productivity from 1.81 tons / day to 2.11 tons / day and a cost reduction of 117.6 dollars / disp. to 110.8 $ / disp.en base to the change of explosive, likewise it was possible to reduce the dilution in a 4.10%.